Dampak Perubahan Layanan Publik Yang Disebabkan Oleh Teknologi Dan Media Sosial - Wahyudi Mokobombang; Syafaruddin Syafaruddin; Andi Riska Andreani Syafaruddin; Khaeriyah Khaeriyah; Nurasia Natsir (Universitas Veteran Bangun Nusantara, 2023)
Technology and social media have brought revolutionary changes in various aspects of human life, including public services. The purpose of this study is to determine the development of technology and social media in changing the way the government and public institutions interact with society and provide public services. This research is Descriptive Research which describes or explains existing phenomena carefully and in detail and can be used to explain changes in public services that occur as a result of the use of technology and social media. Data was collected through surveys, interviews and document analysis to provide an overview. The results of the study show that there are 3 influences of technology and social media on public services in society, including; 1. Technology and social media have a significant influence on the accessibility of public services for the community. 2. Social media has a significant influence on community involvement in public decision-making. 3. The digital divide refers to the gap that occurs between individuals, groups, or regions that have different access and capabilities to information and communication technology.